Pengaruh Pemberian Pupuk Cair Limbah Ikan Lemuru (Sardinella sp.) dengan Dosis yang Berbeda Terhadap Pertumbuhan Chlorella sp. [Effect of Liquit Fertilizer Waste Sardinella Fish (Sardinella sp.) With Different Doses To The Chlorella sp. Growth] - A. Shofy Mubarak; Diana Meritasari; Laksmi Sulmartiwi; Endang Dewi Masithah (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Chlorella sp. can growth in various media that contains enough nutrients, such as N, P, K and other micro-elements. Growth of Chlorella sp. requires the availability of nutrients that can be derived from the chemical decomposition and solution results or waste. Liquid fertilizer waste sardinella fish (Sardinella sp.) is wasted and without any economic value is a new breakthrough in utilizing any part in the fisheries sector so as to maximize the potential of fisheries. Utilization of this, one of which is to make Liquid fertilizer waste sardinella fish (Sardinella sp.) which serve as nutrients for the growth of Chlorella sp. with 7 treatments and repeated 3 times. The treatment used is the doses of liquid fertilizer waste sardinella fish (Sardinella sp.) differently, namely A (0,25 ml/L), B (0,5 ml/L), C (1,75 ml/L), D (1 ml/L), E (1,25 ml/L), F (1,5 ml/L), G (Walne), H (without fertilizer). The results showed that the addition of liquid fertilizer waste sardinella fish (Sardinella sp.) with different doses give a real impact (p<0,05) for growth population of Chlorella sp. The best doses of liquid fertilizer waste sardinella fish (Sardinella sp.) for the population growth rate of Chlorella sp. was 0.75 ml / L is the treatment of C with the highest population of 3500x103 cells / ml.